Telemedicine After The Covid-19 Pandemic A bibliometric analysis and detailed review - Fredericho Mego Sundoro,; Dyah Maya Nihayah,; Retno Febriyastuti Widyawati,; Bintang Satrio Wibowo,; Marcell Pratama Nathaniel, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Indonesia has seen a rapid surge in health tech startups that have disrupted many aspects of the health technology industry. The positive trends have emerged in online pharmacy, telemedicine, and medical education. Telemedicine commonly create similar dividends in other aspects of health facility especially in direct care and treatment. Telemedicine is perceived to have a significant contribution to various aspects of society. One of the domains influenced by this technology is in health infrastructure. A bibliometric analysis used to understand how research and publication in telemedicine in scopus database. Based on a literature review from the scopus database using bibliometric methods and analytical tool such as Vos Viewer and R Studio. A bibliometric analysis presented provides information related to telemedicine themes studied and technological advances in development. In conclusion, the analysis reveals that healthcare research during this period was heavily influenced by the pandemic, with an increasing focus on telemedicine, digital healthcare solutions, and mental health, as well as a consistent use of controlled studies to validate these trends. A research about telemedicine in Indonesia could improve the amount of scientific based review and can lead to a more equitable, efficient, and resilient healthcare system.